Renal coloboma syndrome - Schimmenti, Lisa A (Nature Publishing Group, 2011)
Renal coloboma syndrome (RCS), also called papillorenal syndrome, is an autosomal dominant condition characterized by optic nerve dysplasia and renal hypodysplasia. The eye anomalies consist of a wide and sometimes excavated dysplastic optic disc with the emergence of the retinal vessels from the periphery of the disc, frequently called optic nerve coloboma or morning glory anomaly. Associated findings may include a small corneal diameter, retinal coloboma, scleral staphyloma, optic nerve cyst and pigmentary macular dysplasia. The kidney abnormalities consist of small and abnormally formed kidneys known as renal hypodysplasia. Histologically, kidneys exhibit fewer than the normal number of glomeruli and these glomeruli are enlarged, a finding called oligomeganephronia. Consequences of the ocular malformations include decreased visual acuity and retinal detachment. Consequences of the renal hypodysplasia include hypertension, proteinuria and renal insufficiency that frequently progresses to end-stage kidney disease. High frequency hearing loss has been reported. Autosomal dominant mutations in PAX2 can be identified in nearly half of all patients with clinical findings suggestive of RCS, however, the majority of published cases have mutations in PAX2, thus biasing the known information about the phenotype.